Assistance in Digitalization of Marketing and Customer Satisfaction Programs at MSMEs Batika Indonesia - Nuvriasari, Audita; Mukhorrobin, Ahmad; Harsoyo, Titik Desi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Batik is one of Indonesia's cultural heritages that is already very well-known at the international level and has been designated by UNESCO as an intangible cultural heritage. Technological developments have a strong impact on business strategies carried out by MSMEs, one of which is in the aspect of marketing strategy. The purpose of this community service activity is to assist MSMEs in developing marketing strategies through promotion and measuring customer satisfaction. The activity partner is MSMEs Batika Indonesia, which is mainly engaged in batik bags. The mentoring program implemented is to develop digital marketing content, develop promotional tools and compile instruments to measure customer satisfaction. The achievements of this activity are the increasing variety of digital marketing content and the level of consumer satisfaction is measured.